Advantageous Inequity Aversion Does Not Always Exist: The Role of Determining Allocations Modulates Preferences for Advantageous Inequity - Li, Ou; Xu, Fuming; Wang, Lei (Frontiers in Psychology, 2018)
Previous studies have shown that people would like to sacrifice benefits to themselves in order to avoid inequitable outcomes, not only when they receive less than others (disadvantageous inequity aversion) but also when they receive more (advantageous inequity aversion). This feature is captured by the theory of inequity aversion. The present study was inspired by what appears to be asymmetry in the research paradigm toward advantageous inequity aversion. Specifically, studies that supported the existence of advantageous inequity aversion always relied on the paradigm in which participants can determine allocations. Thus, it is interesting to know what would occur if participants could not determine allocations or simply passed judgment on predetermined allocations. To address this, a behavioral experiment (N = 118) and a skin conductance response (SCR) experiment (N = 29) were adopted to compare participants' preferences for advantageous inequity directly when allocations were determined and when allocations were predetermined in an allocating task. In the determined condition, participants could divide by themselves a sum of money between themselves and a matched person, whereas in the predetermined condition, they could simply indicate their satisfaction with an equivalent program-generated allocation. It was found that, compared with those in the determined condition, participants in the predetermined condition behaved as if they liked the advantageous inequity and equity to the same degree (Experiment One) and that the SCRs elicited by advantageous inequity had no differences from those elicited by equity, suggesting that participants did not feel negatively toward advantageous inequity in this situation (Experiment Two). The present study provided mutual corroboration (behavioral and electrophysiological data) to document that advantageous inequity aversion may differ as a function of the individual's role in determining allocations, and it would disappear if individual cannot determine allocations.